2015
DOI: 10.3923/std.2015.9.15
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Conditions for Pectin Extraction from Citrus Peel

Abstract: Pectin is a complex polysaccharide and natural food additive extracted from citrus peel and apple pomace in the form of brownish powder. It is widely used as a jelling and thickening agent and the food industry especially in jams and jellies. It is also recommended for use as fat replacer and also lowers blood cholesterol by increasing viscosity in the intestinal tract thus lowering cholesterol absorption. Peel of sweet oranges was chopped to small pieces in a vegetable cutter and dried in an electrical drier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
2
9
0
2
Order By: Relevance
“…This compares favorably with the findings of other researchers on pectin yield from orange peels. El-Nawawi and Shehata (1987) and Marin et al (2007) obtained pectin yield between 21-30 and 13-23%, respectively, while Hashmi et al (2012), Kanmani et al (2014), Dehankar et al (2015), and Khan et al (2015) reported maximum pectin yields of 20.12, 29.41, 20, and 21%, respectively. These differences could have been due to the nature of the fruits and extraction process vis-à-vis the processing conditions.…”
Section: Effects Of Processing Factors On Pectin Yieldmentioning
confidence: 96%
See 2 more Smart Citations
“…This compares favorably with the findings of other researchers on pectin yield from orange peels. El-Nawawi and Shehata (1987) and Marin et al (2007) obtained pectin yield between 21-30 and 13-23%, respectively, while Hashmi et al (2012), Kanmani et al (2014), Dehankar et al (2015), and Khan et al (2015) reported maximum pectin yields of 20.12, 29.41, 20, and 21%, respectively. These differences could have been due to the nature of the fruits and extraction process vis-à-vis the processing conditions.…”
Section: Effects Of Processing Factors On Pectin Yieldmentioning
confidence: 96%
“…For oil extraction, extraction temperatures (80,85,90,95, and 100 o C) and extraction times (120,150,180,210, and 240 min) were chosen, while for pectin extraction, extraction temperatures (80,85,90,95, and 100 o C), extraction times (60, 75, 90, 105, and 120 min) and pH (1, 1.5, 2, 2.5, and 3) were selected. The dependent factors considered in this study were considered as the most important factors affecting oil and pectin yield (Gama et al 2015;Khan et al 2015).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using different sources of pectin also resulted in a different amount of moisture content (Castillo-Israel et al, 2015; FULL PAPER Figure 1. Structure of pectin (Khan et al, 2015) Figure 2. Infrared spectra of functional group for dragon fruit peel pectin (a) and commercial pectin (b).…”
Section: Dsc Analysis Of Dragon Fruit Peel Pectinmentioning
confidence: 99%
“…Pectins are naturally occurring water‐soluble complex polysaccharides mainly composed of 1–4 linked α‐ d ‐galacturonic acid and found in citrus, apple, and other higher plants. Pectin is used as stabilizer, thickener, gelling agent, and anticancer drug . Due to the presence of both COOH and OH groups, pectin's hydrogels are more effective in water absorption, metal adsorption, and drug delivery .…”
Section: Introductionmentioning
confidence: 99%